Monitoring system for arc furnace casting processes. (2016) - Cristaldi, Loredana; Clerici, Daniele; Faifer, Marco; Ferrero, Alessandro
The melting process in arc furnaces depends on the presence and propagation of the electric arc between the electrodes and the scrap charge. The heat produced by the arc current melts the scrap to create the molten steel. The characteristics of the electric arc depend mainly on two factors: the 'quality' of the scrap charge and the 'quality' of the electrical supply and components that contribute to the generation of the electric arc. In this paper the correlation between melting process effectiveness and the deviations of the actual electrical quantities from the preset values for different scrap mixtures will be investigated.